A Review of Syngas-Fueled Free Piston Linear Engine Generators: Efficient Fuel Opportunities - Saraban, Salsabila; Md Abu, Hasan Al Askary (INTI International University, 2025)
As global energy consumption continues to rise and conventional fuel sources become scarcer, the need for efficient and sustainable technologies is becoming more urgent. Free piston linear engine generators (FPLGs) are emerging as a viable alternative to conventional engines, offering benefits such as lower friction losses and enhanced efficiency. This paper examines the potential of syngas, an alternative fuel produced through the gasification of biomass, coal, and waste, for powering FPLGs. Syngas stands out due to its broad flammability range, lower emissions, and high hydrogen content, all of which could improve the performance and environmental impact of FPLGs. The review synthesizes data from over 50 peer-reviewed studies published between 2000 and 2024, addressing both the benefits and challenges of using syngas as a fuel. Notable findings include syngas’s high combustion efficiency, reduced emissions compared to conventional fuels, and its suitability for both compression ignition and spark ignition engines. The review further explores syngas’s application in FPLGs, highlighting its effects on combustion efficiency and the environmental advantages of its use. This work provides a thorough overview of how syngas can enhance FPLG efficiency while contributing to cleaner energy solutions.